How to Minimize The Dependency of The Shoe Industry in Indonesia on South Korea - Fu, Then Ngim (Forum Manajemen; Vol 8 No 58 (1994): Forum Manajemen | Integrasi Perdagangan dan Redesain Bisnis Perusahaan Multinasional, 1994)
Since their establishment, most of Indonesian shoe manufactures have been using foreign technolody, especially Korean technology.  (The complete abstracion on the PDF form)